Comparative results of isolated profundoplasty and distal bypass surgery in patients with diabetes mellitus and trophic ulcers - L. A. Bokeria; V. S. Arakelyan; V. G. Papitashvili; S. Sh. Tzurtzumia (Кубанский научный медицинский вестник, 2020)
Aim. To compare the results of lower limb revascularization in patients with diffuse lesions of lower limb arteries who underwent femoral-distal bypass surgery and isolated reconstruction of the deep femoral artery (DFA) in the immediate postoperative period.Materials and methods. The study included 86 patients with diffuse arterial lesions of lower extremities, 52 (60.4%) men and 34 (39.6%) women with the average age of 67.3 ± 16.8 years. All patients had diffuse lesions of the arteries below the Poupart’s ligament; the condition of the lower leg arteries was 5–8.5 points on the Rutherford scale. Trophic ulcers were present in all cases. Group 1 included 48 patients who underwent reconstruction of lower leg arteries. Group 2 included 38 patients whose surgical intervention was limited to endarterectomy from the common femoral and deep femoral arteries.Results. In the early postoperative period, 1 (2.1%) patient (from group 1) died from developed myocardial infarction. The patient underwent a femoral-popliteal-tibial bypass surgery with a composite Y-shaped graft. In group 2, no fatal complications were observed. After the operation, all patients demonstrated an increase in the linear blood flow velocity in the arteries of the foot and the transcutaneous oxygen tension (TOT). The TOT level 14 days after surgery comprised 44.1 mm Hg and 39.9 mm Hg (p> 0.05) in groups 1 and 2, respectively.Conclusions. In 86.8% of patients, isolated profundoplasty followed by vasotropic therapy allows the target values of TOT to be obtained, which is necessary for successful healing of lower limb trophic ulcers.